Semiotika Riffaterre dalam Puisi “Baju Baru” Karya Joko Pinurbo - Abdullah, Risen Dhawuh (MIMESIS, 2024)
It is undeniable that poets often convey ideas with signs in the form of words, clauses, even sentences, thereby creating implicit or implicit messages. Studying a poem requires structural and semiotic analysis, because poetry is a structure of meaningful signs. Joko Pinurbo's poems contain many messages from deep anxiety. This study seeks to explain the meaning of related poetry according to Riffaterre's Semiotics theory. This research is a qualitative descriptive study. The material object in this research is a poem by Joko Pinurbo "Baju Baru". Meanwhile, the formal object is meaning based on language and literary conventions with Riffaterre's Semiotics theory which consists of heuristic readings, hermeneutic readings, as well as matrices, models and variants, hypograms.  The results of the research through heuristic reading analysis found that fathers bought new clothes after payday because fathers' salaries increased. From the hermeneutic reading as a whole, the poem was created by the author as a form of outpouring of his heart as well as a form of criticism of the government for the phenomenon he is seeing, the increase in basic prices that afflict the lower class society, the matrix of the poem is a situation where basic needs soar, while workers' wages only increased slightly or even did not increase. The model of the poem is "gaji bapak" and "presiden". The variants consist of five variants. The first variant is "bapak gajian", the second variant is "reaksi si aku", the third variant is "perasaan presiden", the fourth variant is "kerusakan baju", the fifth variant is "keberadaan tukang becak dan presiden".